A prospective study of work related factors and physical exercise as predictors of shoulder pain. Issue 8 (1st August 2001) - Miranda, H; Viikari-Juntura, E; Martikainen, R; Takala, E-P; Riihimäki, H
Abstract : OBJECTIVES: To evaluate the effects of work related and individual factors as well as physical activity and sports on the incidence and persistence of shoulder pain among forestry workers. METHODS: Workers in a large Finnish forestry company replied to a questionnaire (a modified version of the Nordic questionnaire) on musculoskeletal pain and its possible risk factors for 4 consecutive years 1992–5. This 1 year follow up study covers the time 1994–5. Year 1994 was chosen as baseline because in that year the questionnaire contained for the first time more detailed questions about different sports. The response rate in 1995 was 90%. The effects of the predictors on 1 year incidence and persistence of shoulder pain were studied with multivariate logistic regression modelling. RESULTS: At baseline, 2094 subjects had been free of shoulder pain during the preceding 12 months. After 1 year, 14% (n=285) reported having mild or severe shoulder pain. Higher age, obesity, and mental stress as well as physically strenuous work and working with trunk forward flexed or with a hand above shoulder level increased the risk of incident shoulder pain. Of the different sports activities, dancing increased the risk of incident pain whereas jogging decreased the risk significantly. Of those 419 workers who had severe shoulder pain at baseline, 55% (n=230) still had severe pain 1 year later. Higher age, overload at work, and working with a hand above shoulder level increased the risk of persistent severe shoulder pain whereas cross country skiing and general sports activity decreased the risk. CONCLUSION: Our results support the current view that shoulder pain is the result of many factors, including occupational and individual factors. In this longitudinal study, physical work with a heavy load, awkward work postures, mental stress, and obesity were the risk factors at which preventive measures could be aimed. As a new finding, physical exercise had more protective than impairing effects on the shoulders.